Membrane electrode material based on composite structure anode catalyst layer and preparation and application thereof
By building a composite structure on the anode catalytic layer of the membrane electrode and combining non-precious metals and precious metal catalysts, the problems of low catalyst utilization and high hydrogen content in oxygen are solved, the performance and stability of the electrolytic cell are improved, the cost is reduced, and the Efficient electrolyzing of water to produce hydrogen.
Patent Information
- Application Number
- CN202411423322.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-14
AI Technical Summary
The existing membrane electrode anode catalyst has low utilization rate, high cost, poor stability, and high hydrogen content in oxygen, which affects the performance and safety of the electrolytic cell.
The composite structure anode catalytic layer design is designed, and the proton exchange membrane is coated with non-precious metal catalysts and noble metal catalysts through ultrasonic spraying to form a non-precious metal-containing catalyst layer and noble metal-containing catalyst layer, optimize the catalyst slurry components and structure, and improve the catalyst utilization rate. and electrolytic cell performance.
The hydrogen content in the oxygen in the electrolytic cell is reduced, the performance and stability of the electrolytic cell is improved, the cost is reduced, and the efficient hydrogen production by electrolytic water is achieved, which extends the service life of the electrolytic cell.
Smart Images

Figure CN119307944A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electrode materials, and in particular relates to a membrane electrode material based on a composite structure anode catalyst layer and the preparation and application thereof. Background Art
[0002] Hydrogen energy is a secondary energy with rich application scenarios. It is clean, environmentally friendly, and has high calorific value. It is widely used in transportation, industry, construction, and energy storage. In recent years, with the large-scale development of renewable energy around the world, the global energy structure is accelerating its transformation, and the hydrogen production industry has gradually entered a stage of rapid development. Accelerating the industrial development of hydrogen energy can drive the transformation and upgrading of related energy industries, while reducing dependence on traditional fossil fuels, thereby accelerating the transformation of the energy structure. The electrolysis of water to produce hydrogen technology is regarded as a true "green hydrogen" technology because the production process does not involve the emission of carbon and other toxic and harmful substances. In addition, since hydrogen energy has the dual attributes of power fuel and industrial raw materials, combined with renewable energy electricity, an "electricity-hydrogen" coupling system can be constructed, which can not only reduce the load pressure on the power grid, but also expand green energy to new energy systems in the form of hydrogen energy.
[0003] PEM water electrolysis hydrogen production technology has the advantages of high working efficiency, high current density, high hydrogen purity, fast response speed, etc. It can be coupled with renewable energy and is one of the most promising technologies in water electrolysis hydrogen production technology. The main components of the PEM electrolyzer include collector plate, gas diffusion layer, membrane electrode, flow field plate, and end plate. The membrane electrode is the heart of the PEM electrolyzer and is mainly composed of the anode catalyst layer, PEM, and cathode catalyst layer. It is the main place for electrochemical reactions in the PEM electrolyzer. Its structure and characteristics directly affect the performance and life of the electrolyzer. Summary of the invention
[0004] In view of the defects of the prior art, the technical problem to be solved by the present invention is to provide a membrane electrode material based on a composite structure anode catalyst layer and its preparation and application. The present invention aims to reduce the cost of PEM electrolyzers, improve the performance and stability of PEM electrolyzers, reduce the hydrogen content in anode oxygen and thus improve the safety of electrolyzers, and provides a design of a composite structure anode catalyst layer and its application in a proton exchange membrane electrolyzer. The present invention is based on ultrasonic spraying to coat non-precious metal catalysts in the anode catalyst layer. By constructing an anode catalyst layer with a composite structure, the key problems of low catalyst utilization, high price, poor stability, and high hydrogen content in oxygen in conventional membrane electrode anode catalyst layers are solved.
[0005] The present invention provides a membrane electrode material, which comprises a composite structure anode catalyst layer, a proton exchange membrane layer, and a cathode catalyst layer in sequence; wherein the composite structure anode catalyst layer comprises: a non-precious metal catalyst layer and a precious metal catalyst layer.
[0006] The thickness of the cathode catalyst layer is 4-10 μm, the thickness of the non-precious metal catalyst layer in the anode catalyst layer is 20-200 nm, and the thickness of the precious metal catalyst layer is about 4-8 μm.
[0007] The present invention provides a method for preparing a membrane electrode material, comprising:
[0008] (1) mixing a non-precious metal catalyst, an ion polymer solution, water, and an organic solvent, and ultrasonically dispersing the mixture to obtain a non-precious metal catalyst slurry, which is then coated on a proton exchange membrane to form a non-precious metal catalyst layer;
[0009] (2) mixing and dispersing a noble metal catalyst, an ion polymer solution, water, and an organic solvent to obtain a noble metal catalyst slurry, and then coating the slurry on the non-noble metal catalyst layer to form a composite structure catalyst layer;
[0010] (3) The cathode catalyst, ion polymer solution, water and organic solvent are mixed and ultrasonically dispersed to obtain cathode catalyst slurry, which is then coated on the other side of the proton exchange membrane and subjected to heat pressing to obtain a membrane electrode material.
[0011] Preferably, the non-precious metal catalyst in step (1) is one or more of two-dimensional transition metal compounds (sulfides, oxides, nitrides, etc.); the mass ratio of the non-precious metal catalyst, ionic polymer solution, water, and organic solvent is (0.01-0.03): (0.01-0.1): (7-10): (13-20);
[0012] The ultrasonic dispersion time in step (1) is 20-60 min.
[0013] Preferably, in step (1), a non-precious metal catalyst layer is formed, wherein the non-precious metal catalyst loading is 0.01 to 0.1 mg / cm 2 .
[0014] Preferably, the non-precious metal-containing catalyst includes one or more of MoS2, MS2, MOx, MNx, wherein M is one or more of V, Cr, Mn, Fe, Co, Cu, W, x=1 to 3, and further, x is 1, 2 or 3.
[0015] Preferably, the precious metal catalyst in step (2) is one or more of iridium black, iridium oxide, and ruthenium iridium; wherein the mass ratio of the precious metal catalyst, ion polymer solution, water, and organic solvent is (0.1-0.2): (0.3-1.2): (8-12): (8-15).
[0016] Preferably, the ultrasonic dispersion time in step (2) is 20 to 60 minutes;
[0017] Preferably, in step (2), a composite structure catalyst layer is formed, wherein the noble metal loading is 0.1 to 0.7 mg / cm 2 .
[0018] Preferably, in step (3), the cathode catalyst is a platinum-carbon catalyst, wherein the platinum content is 40-60wt%, and the carbon carrier is one of high specific surface area carbon, XC72, etc.;
[0019] Furthermore, as described in the platinum-carbon catalyst, the platinum content is one of 40wt%, 50wt%, and 60wt%.
[0020] The platinum loading in the membrane electrode material is 0.1-0.5 mg / cm 2 .
[0021] Preferably, in step (3), the mass ratio of cathode catalyst, ionic polymer solution, water and organic solvent is (0.2-0.3): (1.7-2.2): (8-14): (15-20).
[0022] Preferably, the ultrasonic dispersion time in step (3) is 20 to 30 minutes.
[0023] In step (1), a non-precious metal catalyst slurry is coated on a first side of a proton exchange membrane. In step (3), a cathode catalyst slurry is coated on a second side of the proton exchange membrane.
[0024] Preferably, the mass fraction of the ionic polymer solution in steps (1) to (3) is 5 wt% to 20 wt%; and the ionic polymer solution is a perfluorosulfonic acid resin solution.
[0025] Preferably, the organic solvent in steps (1)-(3) is one or more of ethanol, isopropanol, n-propanol, ethylene glycol, and propylene glycol; the water is deionized water; and the coating method is to use a coating device.
[0026] Preferably, in step (3), the hot pressing treatment temperature is 120-160° C., the hot pressing pressure ranges from 1 to 5 MPa, and the hot pressing time ranges from 1 to 10 min.
[0027] In the steps (1) to (3), the coating is performed by uniformly coating the slurry using an ultrasonic spray coater.
[0028] The invention provides a proton exchange membrane PEM electrolyzer, wherein the electrolyzer contains the membrane electrode material.
[0029] Furthermore, the electrolytic cell includes a membrane electrode, a gas transport layer, a flow field plate, and a current collecting plate, which are assembled.
[0030] The present invention provides an application of the membrane electrode material in producing hydrogen by electrolyzing water.
[0031] The present invention assembles the membrane electrode, gas transfer layer, flow field plate, current collecting plate, etc. together for testing to evaluate the performance, stability and other parameters of the membrane electrode in the proton exchange membrane electrolyzer. Compared with the traditional membrane electrode, the design of the composite structure anode catalyst layer shows good performance and stability in the proton exchange membrane electrolyzer test.
[0032] The present invention starts from the design of the catalyst layer structure and obtains a composite structure anode catalyst layer by introducing a non-precious metal catalyst layer. The design of the composite structure anode catalyst layer can improve the membrane electrode performance and reduce the manufacturing cost of the electrolyzer on the one hand, and can reduce the hydrogen content in oxygen and improve the safety of the electrolyzer on the other hand.
[0033] The present invention provides a simple method for preparing a composite structure anode catalyst layer. A thin non-precious metal catalyst layer is first coated on the anode catalyst layer of the membrane electrode, and then a precious metal catalyst layer (such as an iridium-based catalyst layer) is continuously coated on the catalyst layer, and finally a catalyst layer with a composite structure at the anode end of the membrane electrode is obtained. Compared with the conventional structure membrane electrode, the membrane electrode with a composite structure anode catalyst layer described in the present invention not only reduces the amount of precious metal iridium in the PEM electrolyzer and reduces the hydrogen content in the anode oxygen, but also improves the utilization rate of the catalyst in the anode catalyst layer, so that the performance of the electrolyzer is improved and the stability is improved (at 2A / cm 2 The electrolyzer operates stably for more than 400 h at a current density of 2.5 %.
[0034] The present invention achieves high-performance, long-term stable and low-cost membrane electrode preparation by optimizing catalyst slurry components, precious metal dosage distribution, catalyst layer structure, ultrasonic spray coating process and other strategies. In addition, the hydrogen content in oxygen in the PEM electrolyzer directly affects the safety of the electrolyzer.
[0035] Beneficial Effects
[0036] (1) The present invention provides a method for preparing a composite anode catalyst layer, which can effectively reduce the hydrogen content in oxygen in an electrolyzer. (2) The composite anode catalyst layer designed by the present invention realizes the preparation of a low-iridium membrane electrode, improves the electrolysis efficiency of a PEM electrolyzer, and reduces the hydrogen production cost of a PEM electrolyzer (about 15%).
[0037] (3) The composite anode catalyst layer designed by the present invention exhibits excellent catalytic activity and stability in the PEM electrolyzer: as shown in the embodiment, when the iridium loading is 0.5 mg / cm 2 When the voltage is 2V, the current density can reach 4A / cm 2 ; at 1A / cm 2The stability is more than 150h at a current density of 2A / cm 2 At a current density of , the electrolyzer operates stably for more than 400 h. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 A schematic diagram of a composite structure anode catalyst layer;
[0039] Figure 2 Performance comparison of membrane electrode with composite structure anode catalyst layer and traditional membrane electrode;
[0040] Figure 3 (a) and (b) are stability test diagrams of membrane electrodes with composite structure anode catalyst layers at different current densities.
[0041] Figure 4 Performance comparison of composite anode structure membrane electrodes made of two different non-precious metals;
[0042] Figure 5 This is a performance comparison chart of composite anode structure membrane electrodes with different MoS2 loadings. DETAILED DESCRIPTION
[0043] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0044] Example 1
[0045] This embodiment provides a method for preparing a composite structure anode catalyst layer, with a preparation size of 7.5cm×7.5cm and an effective membrane electrode area of 5cm×5cm. The design of the composite structure anode catalyst layer is mainly used in the field of PEM water electrolysis to produce hydrogen.
[0046] (1) 10 mg MoS2 was dispersed in a mixed solvent of 7 g water, 13 g isopropanol, 5 g n-propanol and 0.02 g Nafion (5 wt%) solution, and the catalyst slurry was uniformly dispersed for 40 min using an ultrasonic device. Subsequently, the above slurry was uniformly coated on the PEM using an ultrasonic sprayer, with a spray volume of 4 mL. The MoS2 loading was calculated by weighing to be 0.04 mg / cm 2 .
[0047] (2) 120 mg IrO2 was dispersed in a mixed solvent of 10.1 g isopropanol, 8.22 g water and 0.4 g Nafion (5 wt%) solution, and the mixed slurry was evenly dispersed for 40 min using a cell crusher. The water temperature was controlled below 25°C during the dispersion process. After the dispersion was completed, the slurry was evenly coated on the MoS2 catalyst layer using an ultrasonic sprayer to obtain a composite structure anode catalyst layer. The Ir loading on the membrane was 0.5 mg / cm3 as tested by an X-ray fluorescence spectrometer (XRF). 2 .
[0048] (3) 0.2 g of Pt / C (50 wt%) catalyst was dispersed in a mixed solvent of 16.6 g of isopropanol, 9 g of water and 1.7 g of Nafion (5 wt%) solution, and the mixture was dispersed by ultrasound for 30 min. After the dispersion was completed, the Pt / C slurry was evenly sprayed onto the back of the PEM obtained in step (2) using an ultrasonic sprayer. The spraying area completely corresponded to the anode catalyst layer under the membrane. The XRF test showed that the Pt loading on the membrane was 0.3 mg / cm 2 .
[0049] (4) The membrane electrode obtained in step (3) is hot-pressed at a temperature of 130° C., a pressure of 3 MPa, and a time of 3 min.
[0050] The prepared membrane electrode with composite anode catalyst layer structure was assembled into a PEM electrolyzer with a gas transport layer, flow field plate, current collector plate and end plate. The gas transport layers of the cathode and anode were carbon paper and titanium felt, respectively. The thickness of the carbon paper was 156 μm and the thickness of the titanium felt was 250 μm. After the assembly was completed, the PEM electrolyzer was tested for water flow at a water temperature of 80 °C and then at 0.1 A / cm 2 The activation time was 30 min at a current density of 1 A / cm 2 The cells were activated at a current density of 30 min and at a voltage of 1.7 V for 1 h. After activation was completed, the performance of the PEM electrolyzer was tested.
[0051] The structure of membrane electrode is as follows Figure 1 As shown, one side of the proton membrane is a platinum-carbon coated cathode catalyst layer with a thickness of 6 μm, and the other side is a composite anode catalyst layer, which is composed of non-precious metals and precious metal iridium. The thickness of the non-precious metal catalyst layer is about 70 nm, and the thickness of the precious metal catalyst layer is about 7 μm.
[0052] The performance of the membrane electrode prepared in Example 1 was characterized. Figure 2 The results show that compared with the conventional membrane electrode with a single-layer anode catalyst layer containing only precious metal (Ir), the performance of the membrane electrode with a composite structure anode catalyst layer is better than that of the conventional membrane electrode (iridium loading is 1.2 mg / cm 2), the membrane electrode with composite anode catalyst layer not only reduces the amount of precious metal iridium on the membrane electrode, but also the iridium loading is only 0.50mg / cm 2 , and also improved the performance of the membrane electrode, with a current density of up to 4A / cm at a voltage of 2V 2 .like Figure 3 The figure shows the stability test of the membrane electrode with a composite anode catalyst layer at different current densities. 2 It ran stably for 150 hours under the conditions of 2A / cm 2 The system can run stably for more than 400 hours under the specified conditions.
[0053] Table 1 Comparison of hydrogen content in oxygen between membrane electrode with composite structure anode catalyst layer and traditional membrane electrode
[0054]
[0055] Example 2
[0056] This embodiment is the same as embodiment 1, except that MoS2 is replaced by MS2 and MO x MN x (M=V, Cr, Mn, Fe, Co, Cu, W), other conditions remain unchanged, the membrane electrode performance is as follows Figure 4 As shown, the performance is basically the same as that of Example 1, at 4A / cm 2 At a current density of 1.5 Ω, the voltage deviation is less than 10 mV.
[0057] Example 3
[0058] This embodiment is the same as the embodiment 1, except that IrO2 is changed to one of the catalysts such as iridium black or ruthenium iridium, and the iridium loading on the membrane electrode is kept the same. Other conditions remain unchanged, and are basically the same as the embodiment 1. 2 At a current density of 1.38 W, the voltage deviation is less than 30 mV.
[0059] Example 4
[0060] This example is the same as Example 1, except that the Pt content in the Pt / C catalyst (40 wt%) is changed to 50 wt% or 60 wt%, and other conditions remain unchanged. The membrane electrode performance is basically the same as that in Example 1. 2 At a current density of 1.5 Ω, the voltage deviation is less than 10 mV.
[0061] Example 5
[0062] This example is the same as Example 1, except that the loading of MoS2 is changed by 0.1 mg / cm 2 , other conditions remain unchanged, the membrane electrode performance is as follows Figure 5As shown, the performance is basically the same as that of Example 1, and the voltage deviation is less than 10mV at a current density of 4A / cm2.
[0063] Example 6
[0064] This example is the same as Example 1, except that the IrO2 loading is changed to 0.1 mg / cm 2 Up to 0.7mg / cm 2 , other conditions remain unchanged, the membrane electrode performance is basically the same as in Example 1, at 4A / cm 2 At current densities of 2.5 and 1.3 Å, the voltage varies with the iridium loading.
[0065] Examples 2-5 illustrate that changing a single variable can still produce a membrane electrode with high-performance composite anode catalyst layer structural characteristics.
Claims
1. A membrane electrode material, characterized in that: The membrane electrode material comprises a composite structure anode catalyst layer, a proton exchange membrane layer, and a cathode catalyst layer in sequence; The composite structure anode catalyst layer includes: a non-precious metal catalyst layer and a precious metal catalyst layer.
2. A method for preparing a membrane electrode material, comprising: (1) mixing a non-precious metal catalyst, an ion polymer solution, water, and an organic solvent, and ultrasonically dispersing the mixture to obtain a non-precious metal catalyst slurry, which is then coated on a proton exchange membrane to form a non-precious metal catalyst layer; (2) mixing and dispersing a noble metal catalyst, an ion polymer solution, water, and an organic solvent to obtain a noble metal catalyst slurry, and then coating the slurry on the non-noble metal catalyst layer to form a composite structure catalyst layer; (3) The cathode catalyst, ion polymer solution, water and organic solvent are mixed and dispersed by ultrasonic to obtain cathode catalyst slurry, which is then coated on the other side of the proton exchange membrane and subjected to hot pressing to obtain a membrane electrode material.
3. The preparation method according to claim 2, characterized in that: The non-precious metal catalyst in step (1) is a two-dimensional transition metal compound; the mass ratio of the non-precious metal catalyst, ionic polymer solution, water, and organic solvent is (0.01-0.03): (0.01-0.1): (7-10): (13-20); The ultrasonic dispersion time is 20-60min; In step (1), a non-precious metal catalyst layer is formed, wherein the non-precious metal catalyst loading is 0.01 to 0.1 mg / cm 2 .
4. The preparation method according to claim 3, characterized in that: The non-precious metal-containing catalyst includes one or more of MoS2, MS2, MOx, and MNx, wherein M is one or more of V, Cr, Mn, Fe, Co, Cu, and W, and x=1 to 3.
5. The preparation method according to claim 2, characterized in that: The noble metal catalyst in step (2) is one or more of iridium black, iridium oxide, and ruthenium iridium; wherein the mass ratio of the noble metal catalyst, the ionic polymer solution, water, and the organic solvent is (0.1-0.2): (0.3-1.2): (8-12): (8-15); The ultrasonic dispersion time is 20 to 60 minutes; In step (2), a composite catalyst layer is formed, wherein the noble metal loading is 0.1 to 0.7 mg / cm 2 .
6. The preparation method according to claim 2, characterized in that: In step (3), the cathode catalyst is a platinum-carbon catalyst, wherein the platinum content is 40-60 wt %; wherein the mass ratio of the cathode catalyst, the ionic polymer solution, water, and the organic solvent is (0.2-0.3): (1.7-2.2): (8-14): (15-20); The ultrasonic dispersion time is 20 to 30 minutes; the platinum loading in the membrane electrode material is 0.1 to 0.5 mg / cm 2 .
7. The preparation method according to claim 2, characterized in that: The mass fraction of the ionic polymer solution in steps (1) to (3) is 5wt% to 20wt%; the ionic polymer solution is a perfluorosulfonic acid resin solution; The organic solvent in steps (1) to (3) is one or more of ethanol, isopropanol, n-propanol, ethylene glycol, and propylene glycol; and the water is deionized water.
8. The preparation method according to claim 2, characterized in that: In the step (3), the hot pressing treatment temperature is 120-160° C., the hot pressing pressure ranges from 1 to 5 MPa, and the hot pressing time ranges from 1 to 10 min.
9. A PEM electrolyzer, characterized in that: The electrolytic cell contains the membrane electrode material according to claim 1.
10. Use of the membrane electrode material according to claim 1 in producing hydrogen by electrolysis of water.